Kumar & Clark's Cases in clinical medicine - Kumar, Parveen J. (Parveen June); Clark, Michael L. (Edinburgh ; New York : Saunders Elsevier, 2013)
1. Infectious Diseases -- 2. Sexually Transmitted Infections -- 3. Nutrition -- 4. Gastroenterology -- 5. Liver and Bilary Tract Disorders -- 6. Haematology and Oncology -- 7. Care of the Elderly -- 8. Rheumatology -- 9. Kidney and Urinary Tract Disease -- 10. Cardiology -- 11. Respiratory Disorders -- 12. ITU -- 13. Poisoning -- 14. Endocrinology and Diabetes -- 15. Neurology -- 16. Psychiatry -- 17. Dermatology.
1. Infectious Diseases -- 2. Sexually Transmitted Infections -- 3. Nutrition -- 4. Gastroenterology -- 5. Liver and Bilary Tract Disorders -- 6. Haematology and Oncology -- 7. Care of the Elderly -- 8. Rheumatology -- 9. Kidney and Urinary Tract Disease -- 10. Cardiology -- 11. Respiratory Disorders -- 12. ITU -- 13. Poisoning -- 14. Endocrinology and Diabetes -- 15. Neurology -- 16. Psychiatry -- 17. Dermatology.
Includes index.
Keywords: Clinical Medicine -- case reports